Kamal Hassan’s vision for holistic education at IIUM - Ali, Mohd Mumtaz; Abdul Razak, Mohd Abbas (Human Assistance & Development International Inc. (HADI Inc.), 2025)
In the 1980s, Malaysian Islamic scholar Mohd Kamal Hassan was commissioned by Malaysia’s Prime Minister to draft a concept paper for establishing the International Islamic University Malaysia (IIUM). Known for his balanced and comprehensive grasp of Islam, Kamal Hassan conceptualized IIUM with a robust philosophical, epistemological, and ideological foundation. His vision framed Islam as a holistic way of life, shaping the university’s mission to promote peace and harmony within the Muslim community and beyond.